TEACHING ACADEMIC WRITING TO ESL STUDENTS: TIPS AND TECHNIQUES (International journal of artificial intelligence, 2024)
Teaching academic writing to ESL (English as a Second Language) students is essential for helping them develop the necessary skills to succeed in higher education or professional environments. This process involves understanding key writing structures, improving language proficiency, and becoming familiar with academic conventions. To support ESL students, educators should focus on teaching the fundamentals of essay structure, from introductions and thesis statements to body paragraphs and conclusions. Additionally, expanding students' academic vocabulary and helping them understand the use of cohesive devices is crucial for clarity and coherence. This article explores various techniques and strategies that can effectively enhance the academic writing skills of ESL students.